An empirical study of customers’ adoption of mobile money transfer services in Somaliland - Oyefolahan, Ishaq Oyebisi; Abubakar, Adamu; Ahmed, Sa’ad Abdirisak (2014)
This paper investigates factors influencing customers’ adoption of Mobile Money Transfer Services in Somaliland by applying and extending the Technology Acceptance Model (TAM) model. We proposed and tested statistical hypotheses based on the data collected from 204 respondents who are customers that use the “Zaad” Mobile Money Transfer Services operated by Telsom Telecommunication Company in Somaliland. By testing the influence of Perceived Ease of Use, Perceived Usefulness and Perceived Trust (all moderated by gender) on the Behavioral Intention to adopt the “Zaad service”, the results of the study further confirms that all the aforementioned factors are important determinants of Intention to Use while no significant difference was found between the genders. Finally, implications and a brief conclusion is presented.